the PARADOXES of MOURNING : healing your grief with three forgotten truths - Wolfelt, Alan D. (Fort Collins, Colorado : Companion Press, an imprint of the Center for Loss and Life Transition, 2023)
When it comes to healing after the death of someone loved, our culture has it all wrong. We're told to be strong when what we really need is to be vulnerable. We're told to think positive when what we really need is to wallow in the pain. And we're told to seek closure when what we really need is to welcome our natural and necessary grief. Wolfelt seeks to dispel these misconceptions, and help people everywhere mourn well so they can live fuller lives.
Keywords: Grief; Bereavement